Accessibility Evaluation: UEQ Principles in User Interface Design for Persons with Dyslexia and Color Blindness - Gurbanova, Aytan (ADA University, 2024)
This paper aims to analyze the challenges encountered by dyslexic and color blind individuals in their use of mobile applications by developing evaluation metrics based on the UEQ principles to ensure accessibility. The study involved testing a mobile application called “HNK Bank” with people from three different groups: those that are dyslexic, those with color blindness, and those who don’t have either condition. The application was designed for persons with dyslexia and color blindness in terms of appropriate fonts and color choices. During the evaluation process, each user was instructed to perform four scenarios with no intervention from our side, and we measured the time of testing each scenario individually. Following the testing, a brief interview was done with each, involving a wide range of questions about the application. Overall, the participants found the application easy to use and did not encounter much difficulty regarding reading and understanding. This indicates that choosing the right color and font options leads to good accessibility. However, the dyslexic group took longer to complete the scenarios compared to the other two groups, mainly because they need more time to process the information. Participants also shared a few ideas for future improvement of the application. The most common suggestion was the addition of the Azerbaijani language. This suggestion was primarily influenced by the fact that for some individuals, learning a second language can be quite challenging, especially those with dyslexia. We also observed an obvious pattern in likes and suggestions and the users’ corresponding conditions. Meaning, the users with dyslexia mostly mentioned font-related features, while color blind people focused on color-related features. The study demonstrated that by implementing suitable design considerations, technology can provide accessibility to any users regardless of their conditions. However, considering the current simplicity of the application, it is possible that when the application is further enhanced, accessibility might diminish. Therefore, it is utmost important that when the application equips more functionalities based on user suggestions, it should still maintain accessibility features.
Keywords: Color blindness -- Technology; Mobile applications -- Accessibility; Human-computer interaction; Web accessibility; User experience (UX) -- Evaluation; IT and Engineering